Sphaerospora sensu stricto: taxonomy, diversity and evolution of a unique lineage of myxosporeans (Myxozoa) - Bartošová, Pavla; Fiala, Ivan; Jirků, Miloslav; Cinková, Martina; Caffara, Monica; Fioravanti, Maria Letizia; Atkinson, Stephen Douglas; Bartholomew, Jerri Lee; Holzer, Astrid Sibylle (Molecular phylogenetics and evolution, 2013)
Myxosporeans (Myxozoa) are eukaryotic parasites, primarily of fish, whose classification is in a state of flux as taxonomists attempt to synthesize the traditional morphology-based system with emerging DNA sequence-based phylogenies. The genus Sphaerospora Thélohan, 1892, which includes pathogenic species that cause significant impacts on fisheries and aquaculture, is one of the most polyphyletic taxa and exemplifies the current challenges facing myxozoan taxonomists. The type species, S. elegans, clusters within the Sphaerospora sensu stricto clade, members of which share similar tissue tropism and long insertions in their variable rRNA gene regions. However, other morphologically similar sphaerosporids lie in different branches of myxozoan phylogenetic trees. Herein, we significantly extend taxonomic sampling of sphaerosporids with SSU+LSU rDNA and EF-2 sequence data for 12 taxa including three representatives of the morphologically similar genus Polysporoplasma Sitjà-Bobadilla et Álvarez-Pellitero, 1995. These taxa were sampled from different vertebrate host groups, biogeographic realms and environments. Our phylogenetic analyses and statistical tests of single and concatenated datasets revealed Sphaerospora s. s. as a strongly supported monophyletic lineage, that clustered sister to the whole myxosporean clade (freshwater+marine lineages). Generally, Sphaerospora s. s. rDNA sequences (up to 3.7 kb) are the longest of all myxozoans and indeed metazoans. The sphaerosporid clade has two lineages, which have specific morphological, biological and sequence traits. Lineage A taxa (marine Sphaerospora spp.) have a single binucleate sporoplasm and shorter AT-rich rDNA inserts. Lineage B taxa (freshwater/brackish Sphaerospora spp.+marine/brackish Polysporoplasma spp.) have 2-12 uninucleate sporoplasms and longer GC-rich rDNA inserts. Lineage B has four subclades that correlate with host group and habitat; all Polysporoplasma species, including the type species, cluster together in one of these subclades. We thus suppress the genus Polysporoplasma and the family Polysporoplasmidae and emend the generic diagnosis of the genus Sphaerospora. The combination of morphological, biological and DNA sequence data applied in this study helped to elucidate an important part of the taxonomic puzzle within the phylum Myxozoa.
Keywords: zastoupení bazí; velké ribozomální podjednotky; elongační faktor 2; malé podjednotky ribozomu; Fish Diseases; Peptide Elongation Factor 2; genetická variace; fylogeneze; Sequence Analysis, DNA; Ribosome Subunits, Small; Phylogeny; ribozomální DNA; sekvenční analýza DNA; biologická evoluce; Ribosome Subunits, Large; Myxozoa; ryby; Fishes; Animals; Biological Evolution; zvířata; nemoci ryb; Base Composition; DNA, Ribosomal; Genetic Variation